Avaliação do efeito da adição de opacificantes na microestrutura de cerâmicas refratárias macroporosas - Santos, Príscylla Ferreira dos (Universidade Federal de São Carlos, 2023)
The refractory ceramic materials used in thermal insulation can be classified into three large groups: insulating bricks and concrete, fiber-based refractories and macroporous ceramics. Such macroporous ceramics, commonly present high porosity, controlled permeability, high chemical and dimensional stability at high temperatures, low density, and have aroused technological interest. Opacifying agents (e.g. SiC, TiO2, ZrSiO4) are usually added to macroporous refractory ceramics with the aim of increasing the absorption of infrared radiation and reducing the thermal conductivity in order to reduce the heat transfer by radiation and the conductivity total thermal at high temperatures. However, the introduction of these additives can generate side effects to the material properties. Thus, the present work aimed to obtain a better understanding of the manufacture of macroporous ceramics by the direct foaming processing route, as well as to evaluate the properties of macroporous ceramics based on alumina regarding the addition of opacifying agents ZnO, TiO2, Nb2O5 and the combination between them, being ZnO-TiO2 (equimolar) in concentrations of up to 2.8 mol%. For this, the different compositions were characterized according to their post-burning linear variation, total porosity, mechanical resistance, apparent density, quantitative mineralogical composition, refractoriness under load and microstructural analysis from the scanning electron microscope.
Evaluation of the effect of the addition of opacifiers on the microstructure of macroporous refractory ceramics
Keywords: Cerâmica refratária; Macroporosos; Opacificantes; Refractory ceramics; Macroporous; Opacifiers; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS